2012
DOI: 10.1515/cjal-2012-0008
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of the Use of Wikis in English Language Learning

Abstract: This paper presents a study exploring the efficacy of Wikis in an online language exchange program involving a purposeful sample of university students from China and the UK. The article first provides a brief overview of the use of Web 2.0 applications in language education. It then specifically addresses the potential advantages of using Wikispaces in second language acquisition, particularly in tasks designed for the purpose of collaborative learning. Research methods employed in the study included question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Example s of Web 2.0 applications used in education include blogs, podcasts, tags, iBooks, Wikis, YouTube, Teacher Tube, Facebook, MySpace, Flicker and Twitter. A number of studies were conducted to investigate the use of Web 2.0 applications in different teaching contexts (Albarbari, 2016; Balcikanli, 2012; Batsila et al , 2015; Dang and Robertson, 2010; Duffy and Bruns, 2006; Garofalakis, Lagiou and Plessas, 2013; Joseph, 2013; Light and Polin, 2010; Raymond, 2010; Shih, 2011; Thomson, 2007; Vurdien, 2013; Wetzel, 2009; Zhang, 2010; Zou et al , 2012).…”
Section: The Use Of Web 20 In Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…Example s of Web 2.0 applications used in education include blogs, podcasts, tags, iBooks, Wikis, YouTube, Teacher Tube, Facebook, MySpace, Flicker and Twitter. A number of studies were conducted to investigate the use of Web 2.0 applications in different teaching contexts (Albarbari, 2016; Balcikanli, 2012; Batsila et al , 2015; Dang and Robertson, 2010; Duffy and Bruns, 2006; Garofalakis, Lagiou and Plessas, 2013; Joseph, 2013; Light and Polin, 2010; Raymond, 2010; Shih, 2011; Thomson, 2007; Vurdien, 2013; Wetzel, 2009; Zhang, 2010; Zou et al , 2012).…”
Section: The Use Of Web 20 In Educationmentioning
confidence: 99%
“…Zou et al (2012) studied using Web 2.0 tools in learning language among 291 students. They found that Web 2.0 tools such as blogs, social networking, Wikis and Podcasts provide opportunities for students to discuss language learning materials through online resources and offer opportunities to communicate with people at large distances through the internet.…”
Section: The Use Of Web 20 In Educationmentioning
confidence: 99%
“…2; 2010). Moreover, wikis provided authentic interaction between university students across countries (Zou et al, 2012).…”
Section: Interaction On Wikismentioning
confidence: 99%